Academic Advisors in the Completion of Undergraduate Study: The Role of Arabic Language Lecturers - Wa Muna; Miftahul Huda; Syuhadak Syuhadak (STAI Hubbulwathan Duri, 2022)
This study aims to investigate the role of Arabic language lecturers as academic advisors in the IAIN Kendari students' completion process. Using four faculties as the location for this study, snowball sampling was used to select eight students and nine Arabic lecturers for separate interviews and observations during the consultation process in the 2020/21 academic year. The data analysis phase was conducted using the Miles and Huberman method and the Academic Advisor theory. As academic advisors, the results indicate that Arabic language lecturers play three crucial roles: motivators, initiators, and problem solvers. This research has implications for academic advising policies and on-time student graduation.